Mettray : a history of France's most venerated carceral institution - Toth, Stephen A. (Cornell University Press, 2019)
"By examining Mettray's "history from below" (i.e., from the perspective of prisoners and staff) this book illuminates the heretofore hidden life of France's most venerated carceral institution"--